Low muscle strength and low phase angle predicts greater risk to mortality than severity scales (APACHE, SOFA, and CURB-65) in adults hospitalized for SARS-CoV-2 pneumonia - Rosas-Carrasco, Oscar; Núñez-Fritsche, Gisela; López-Teros, Miriam Teresa; Acosta-Méndez, Pamela; Cruz-Oñate, Juan Carlos; Navarrete-Cendejas, Ada Yuseli; Delgado-Moreno, Gerardo (Frontiers in Nutrition, 2022)
Introduction: The APACHE, SOFA, CURB-65 scales, a low phase angle (PA) and low muscle strength (MS) have demonstrated their prognostic risk for mortality in hospitalized adults. However, no study has compared the prognostic risk between these scales and changes in body composition in a single study in adults with SARS-CoV-2 pneumonia. The great inflammation and complications that this disease presents promotes immobility and altered nutritional status, therefore a low PA and low MS could have a higher prognostic risk for mortality than the scales. The aim of the present study was to evaluate the prognostic risk for mortality of PA, MS, APACHE, SOFA and CURB-65 in adults hospitalized with SARS-CoV-2 pneumonia. Methodology: This was a longitudinal study that included n=104 SARS-CoV-2-positive adults hospitalized at Pénjamo-Guanajuato General Hospital, Mexico, The PA was assessed using bioelectrical impedance and MS was measured with manual dynamometry. The following disease severity scales were applied as well: CURB-65, APACHE and SOFA. Other variables analyzed were: sex, age, CO-RADS index, fat mass index BMI, and appendicular muscle mass index. A descriptive analysis of the study variables and a comparison between the group that did not survive and survived were performed, as well as a Cox regression to assess the predictive risk to mortality. Results: Mean age was 62.79 ± 15.02 years (31-96). Comparative results showed a mean PA of 5.43 ± 1.53 in the group that survived vs. 4.81 ± 1.72 in the group that died, p=0.030. The mean MS was 16.61 ± 10.39 kg vs. 9.33 ± 9.82 in the group that died, p=0.001. The cut-off points for low PA was determined at 3.66° and ≤5.0 kg/force for low grip strength. In the Cox multiple regression, a low PA (HR = 2.571 0.726, 95% CI=1.217-5.430) and a low MS (HR= 4.519, 95% CI=1.992-10.252) were associated with mortality. Conclusion: PA and MS were higher risk predictors of mortality than APACHE, SOFA, and CURB-65 in patients hospitalized for COVID-19. It is important to include the assessment of these indicators in patients positive for SARS-CoV-2 and to be able to implement interventions to improve them.